Management of acute stroke. Specific nursing care and treatments in the stroke unit - E. Sanjuan; O. Pancorbo; K. Santana; O. Miñarro; V. Sala; M. Muchada; S. Boned; J.M. Juega; J. Pagola; Á. García-Tornel; M. Requena; N. Rodríguez-Villatoro; et al. (Neurología (English Edition), 2023)
Objective: This study provides a series of updated, evidence-based recommendations for the management of acute stroke. We aim to lay a foundation for the development of individual centres’ internal protocols, serving as a reference for nursing care. Methods: We review the available evidence on acute stroke care. The most recent national and international guidelines were consulted. Levels of evidence and degrees of recommendation are based on the Oxford Centre for Evidence-Based Medicine classification. Results: The study describes prehospital acute stroke care, the operation of the code stroke protocol, care provided by the stroke team upon the patient’s arrival at hospital, reperfusion treatments and their limitations, admission to the stroke unit, nursing care in the stroke unit, and discharge from hospital. Conclusions: These guidelines provide general, evidence-based recommendations to guide professionals who care for patients with acute stroke. However, limited data are available on some aspects, showing the need for continued research on acute stroke management. Resumen: Objetivo: Proporcionar un conjunto de recomendaciones actualizadas y basadas en la evidencia disponible para el manejo del ictus agudo. Nuestro objetivo es proporcionar una base para el desarrollo de los protocolos internos de cada centro, sirviendo de referencia para los cuidados de enfermería. Métodos: Revisión de evidencias disponibles sobre los cuidados del ictus agudo. Se han consultado las guías nacionales e internacionales más recientes. Los niveles de evidencia y grados de recomendación se han basado en la clasificación del Centro de Medicina Basada en la Evidencia de Oxford. Resultados: Se describen la atención y los cuidados del ictus agudo en la fase prehospitalaria, el funcionamiento de código ictus, la atención por el equipo de ictus a la llegada al hospital, los tratamientos de reperfusión y sus limitaciones, el ingreso en la unidad de ictus (UI), los cuidados de enfermería en la UI y el alta hospitalaria. Conclusiones: Estas pautas proporcionan recomendaciones generales basadas en la evidencia actualmente disponible para guiar a los profesionales que atienden a pacientes con ictus agudo. En algunos casos, sin embargo, existen datos limitados demostrando la necesidad de continuar investigando sobre el manejo del ictus agudo.